2013
DOI: 10.1037/a0029558
|View full text |Cite
|
Sign up to set email alerts
|

Language and literacy development of deaf and hard-of-hearing children: Successes and challenges.

Abstract: Childhood hearing loss presents challenges to language development, especially spoken language. In this article, we review existing literature on deaf and hard-of-hearing (DHH) children's patterns and trajectories of language as well as development of theory of mind and literacy. Individual trajectories vary significantly, reflecting access to early identification/intervention, advanced technologies (e.g., cochlear implants), and perceptually accessible language models. DHH children develop sign language in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
233
2
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(272 citation statements)
references
References 150 publications
11
233
2
10
Order By: Relevance
“…From the results, lack of mastery of reading comprehension at sentence level is a contributor to the learners' low functioning level in expressive written English. The finding is consistent with Lederberg, Schick and Spencer (2012) and Moeller, Tomblin, Yoshinaga-Itano, Conner and Jerger (2007) who found that PRE-LD learners lacked mastery of reading comprehension at sentence level to be able to write a comprehensive text. However, the current finding specifically shows the sentence type the learners are unable to read and understand to facilitate expression at text level by the end of Class III.…”
Section: Fig3: An Excerpt Of Showing a Guided Composition By A Prelisupporting
confidence: 81%
“…From the results, lack of mastery of reading comprehension at sentence level is a contributor to the learners' low functioning level in expressive written English. The finding is consistent with Lederberg, Schick and Spencer (2012) and Moeller, Tomblin, Yoshinaga-Itano, Conner and Jerger (2007) who found that PRE-LD learners lacked mastery of reading comprehension at sentence level to be able to write a comprehensive text. However, the current finding specifically shows the sentence type the learners are unable to read and understand to facilitate expression at text level by the end of Class III.…”
Section: Fig3: An Excerpt Of Showing a Guided Composition By A Prelisupporting
confidence: 81%
“…The findings concurred with Lederberg, Schick and Spencer (2012), Lederberg and Spencer (2001), Weizerman andSnow (2001), William, (2012) who found that Elementary School PRE-LD learners were limited in the use of vocabulary in written language. The current study, however, showed the specific verb and adjectival phrases that PRE-LD learners lacked by the end of Class III.…”
Section: Construction Of Simple Sentences Using Verb and Adjectival Psupporting
confidence: 79%
“…The finding concurred with Berent (1993Berent ( ,2001), Lederberg,Schick & Spencer(2012, Marschark & Knoor (2012, Moeller, Tomblin,Yoshinaga-Itano, Conner & Jerger (2007;Quigley and King,1980;Wilbur and Quigley, 1975 )which also showed that Elementary school PRE-LD learners were deficient in sentence construction. The current study, however, specifically showed the compound sentences that PRE-LD learners who had not been exposed to language during CLAP.…”
Section: Mastery Of Construction Of Compound Sentencessupporting
confidence: 78%
“…The beneficial impact of early intervention on language for children with permanent hearing loss has been demonstrated (Meinzen‐Derr, Wiley, & Choo, 2011). However, there is a paucity of evaluation studies to identify optimal intervention strategies to enhance language in the deaf population (Lederberg et al., 2013). …”
Section: Discussionmentioning
confidence: 99%